OFDM-IDMA Uplink Multi-user System with Scalable Latency for Next Generation WLAN - Leonardo Alisasis Lanante; Nguyen Tran Thi Thao; Yuhei Nagao; Hiroshi Ochi (EPI International Journal of Engineering, 2020)
In this paper, we propose an Interleave-Division Multiple Access (IDMA) based uplink multi-user system fornext generation WLAN. By minimizing the latency throughaccurate detection per iteration, we were able to design a receiver architecture that meets the latency demands of current IEEE802.11 WLAN. To do this, the proposed system utilizes a novel algorithm for simplified LLR calculation of the soft input soft output demapper needed in the IDMA first stage detection.The proposed system has a maximum of 34.8 bits/s/Hz spectral efficiency for a single spatial stream and can support up to 8 users in a single 20MHz channel. We compare the proposed system to a reference OFDMA system and show its advantages in terms of diversity, flexibility and BER performance. Keywords: 802.11ax; IDMA; uplink multi-user access